Properties of large organic molecules on metal surfaces - Rosei, Federico; Schunack, Michael; Naitoh, Yoshitaka; Jiang, Ping; Gourdon, André; Laegsgaard, Erik; Stensgaard, Ivan; Joachim, Christian; Besenbacher, Flemming (Progress in surface science, 2003)
The adsorption of large organic molecules on surfaces has recently been the subject of intensive investigation, both because of the molecules’ intrinsic physical and chemical properties, and for prospective applications in the emerging field of nanotechnology. Certain complex molecules are considered good candidates as basic building blocks for molecular electronics and nanomechanical devices. In general, molecular ordering on a surface is controlled by a delicate balance between intermolecular forces and molecule–substrate interactions. Under certain conditions, these interactions can be controlled to some extent, and sometimes even tuned by the appropriate choice of substrate material and symmetry. Several studies have indicated that, upon molecular adsorption, surfaces do not always behave as static templates, but may rearrange dramatically to accommodate different molecular species. In this context, it has been demonstrated that the scanning tunnelling microscope (STM) is a very powerful tool for exploring the atomic-scale realm of surfaces, and for investigating adsorbate–surface interactions. By means of high-resolution, fast-scanning STM unprecedented new insight was recently achieved into a number of fundamental processes related to the interaction of largish molecules with surfaces such as molecular diffusion, bonding of adsorbates on surfaces, and molecular self-assembly. In addition to the normal imaging mode, the STM tip can also be employed to manipulate single atoms and molecules in a bottom–up fashion, collectively or one at a time. In this way, molecule-induced surface restructuring processes can be revealed directly and nanostructures can be engineered with atomic precision to study surface quantum phenomena of fundamental interest. Here we will present a short review of some recent results, several of which were obtained by our group, in which several features of the complex interaction between large organic molecules and metal surfaces were revealed. The focus is on experiments performed using STM and other complementary surface-sensitive techniques.